Testing and debugging functional reactive programming - Perez, Ivan; Nilsson, Henrik (Association for Computing Machinery, 2017)
Many types of interactive applications, including video games, raise particular challenges when it comes to testing and debugging. Reasons include de-facto lack of reproducibility and difficulties of automatically generating suitable test data. This paper demonstrates that certain variants of Functional Reactive Programming (FRP) implemented in pure functional languages can mitigate such difficulties by offering referential transparency at the level of whole programs. This opens up for a multi-pronged approach for assisting with testing and debugging that works across platforms, including assertions based on temporal logic, recording and replaying of runs (also from deployed code), and automated random testing using QuickCheck. The approach has been validated on real, non-trivial games implemented in the FRP system Yampa through a tool providing a convenient Graphical User Interface that allows the execution of the code under scrutiny to be controlled, moving along the execution time line, and pin-pointing of violations of assertions on PCs as well as mobile platforms.